A qualitative study on South African policies governing youth access to alcohol - Matee, Larona (Department of Social Development, 2025)
Alcohol abuse among youth continues to be a major concern worldwide in the 21st century. It has been suggested in various studies that the age of onset is decreasing rapidly and that admissions to treatment centres are increasing as young people fall prey to substance abuse. This raises serious concerns as alcohol abuse is linked to adverse health outcomes such as physical and mental health problems, social and legal consequences, as well as economic burdens. Zwelihle, a township in Hermanus, is one such community that faces various social issues, including high rates of alcohol abuse amongst the youth. This study used a qualitative research design based on the interpretivist position. Data were collected from twenty participants using a semi-structured interview guide. Fifteen young participants (aged 18 to 35) took part in focus groups, and five professionals with experience working with Zwelihle's youth were interviewed one-on-one. Data were analyzed following Tesch's qualitative data analysis steps. The study results revealed that factors such as a lack of parental involvement, unemployment, socialisation and culture as well as the availability of limited recreational activities were identified to be prominent factors which led Zwelihle's youth to alcohol and the abuse thereof. Other factors, such as alcohol outlet concentration and density in Zwelihle were argued to be one of the factors that facilitates easy access to alcohol in Zwelihle. This is also caused by the plight which comes with heightened levels of unemployment in South Africa, which drives people to alcohol dependency to forget and escape their harsh realities, or people open shebeens as a response to the harsh economic realities. At the backdrop of these concerns were the various alcohol trading policies, which were said to be ineffective in regulating the alcohol trade, and which have resulted in almost every street in Zwelihle having someone trading in alcohol and selling it to young people. One of the reasons participants cited for the failing alcohol policies was due to unreliable law enforcement agencies who were perceived to be corrupt